Assessing the chemical and microbiological quality of farmed tilapia in Egyptian fresh fish markets - Eltholth, Mahmoud; Fornace, Kimberly; Grace, Delia; Rushton, Jonathan; Häsler, Barbara (Elsevier, 2018)
Fish make important contributions to food and nutrition security in low and middle income countries; however, they are also prone to contamination with a range of chemical and biological hazards. The presence of people's perception and health hazards has implications for consumer acceptability and hence the potential contribution of fish to nutrition and health. The aim of this study was to assess the chemical and microbiological quality of farmed tilapia in Egypt. We conducted a systematic literature review resulting in 38 papers meeting inclusion criteria. We also conducted a survey of seven hazardous chemicals in fish sampled from farms (300 samples from 100 farms) and of 5 biological hazards as well as total bacterial counts in fish sampled from retailers (300 samples from 100 retailers). The results showed that the level of contamination with heavy metals and pesticides was lower than the national and international permissible limits. On the other hand, level of contamination of a considerable proportion of samples with microbial pollutants was higher than the permissible limits. Results from the literature indicated that, the level of contamination of wild tilapia was higher than farmed tilapia, again in contradiction to common perceptions. Our results indicate that the risk of human exposure to heavy metals and pesticides via consumption of farmed tilapia is negligible compared to microbial hazards. These findings suggest that post-harvest contamination is the major health risk in the tilapia fish value chain and we make recommendations for addressing this.